How split-feed osmotically assisted reverse osmosis (SF-OARO) can outperform conventional reverse osmosis (CRO) processes under constant and varying electricity tariffs - Mo, Zijing (2022)
Improving the recovery of desalination processes can have economic benefits, as feed and brine volumes are minimised. Furthermore, brine volume minimisation (BVM) simplifies brine treatment prior to disposal and hence, alleviates potential environmental concerns. However, BVM is not widely applied, as it is generally more energy intensive and costly. This may change in the future, as new high-recovery membrane processes, such as split-feed osmotically assisted reverse osmosis (SF-OARO), can potentially lower the required operating pressure and the energy consumption associated with brine dewatering via osmotic counterbalance. In addition, the added flexibility of OARO integrated systems may further reduce the unit water cost (UWC) in regions with varying-electricity tariffs. To verify these hypothesised advantages of OARO, this study explores the economic and technical viability of SF-OARO. Under constant electricity tariffs, the results indicate that the optimized SF-OARO process can achieve a higher process recovery (65% versus 50%) while operating at a 4.1% lower UWC than conventional RO (CRO), when assuming an intermediate brine disposal cost of 0.3 $/m3. This cost advantage of SF-OARO further expands under operation with varying-electricity tariffs. In summary, the presented results indicate that the SF-OARO process is the preferred and cheaper choice once the brine disposal cost exceeds 0.21 $/m3 of brine.